2020
DOI: 10.1002/ijgo.13108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early second‐look hysteroscopy combined with intrauterine balloon dilatation on reproductive outcomes for women with intrauterine adhesions

Abstract: Objective:To investigate the effect of early second-look office hysteroscopy combined with intrauterine balloon dilatation on prognosis and pregnancy rate for women with intrauterine adhesions. Methods:A retrospective analysis of 156 women diagnosed with intrauterine adhesions by hysteroscopy at Shenyang Women's and Children 's Hospital, China, from April 2017 to January 2019. The study women underwent intrauterine balloon dilatation 10 days after transcervical resection of adhesion (TCRA) and hysteroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…After TCRA, placing an IUB can not only block the adhesion of different uterus wall, it is also convenient for drainage of hematometra and in ammatory exudation in uterine cavity, which contribute to minimize the risk of infection and reduce the recurrence rate of intrauterine adhesion. Other study found that menstruation of up to 81.4% IUA patients had improved, who were placed IUB after surgery [1], and the overall conception rate was 33.9%-48.1%, the recurrence rate of IUA after surgery was 13.6%-38.7% [9][10][11][12][13]. Compared with placing IUD after TCRA, IUB could lead to a lower adhesion AFS score and in the meantime result in a lower recurrence rate [1], which was entirely consistent with the results in this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…After TCRA, placing an IUB can not only block the adhesion of different uterus wall, it is also convenient for drainage of hematometra and in ammatory exudation in uterine cavity, which contribute to minimize the risk of infection and reduce the recurrence rate of intrauterine adhesion. Other study found that menstruation of up to 81.4% IUA patients had improved, who were placed IUB after surgery [1], and the overall conception rate was 33.9%-48.1%, the recurrence rate of IUA after surgery was 13.6%-38.7% [9][10][11][12][13]. Compared with placing IUD after TCRA, IUB could lead to a lower adhesion AFS score and in the meantime result in a lower recurrence rate [1], which was entirely consistent with the results in this study.…”
Section: Discussionmentioning
confidence: 95%
“…According to the 1988 American Fertility Society (AFS) scoring system [6], patients with IUA are divided into three stages, designed as mild(a score of 1-4), moderate(a score of 5-8) and severe(a score of [9][10][11][12]. This classi cation standard evaluates the extent of cavity involved, type of adhesion and menstrual pattern of patients during hysteroscopic surgery.…”
Section: Operationmentioning
confidence: 99%
“…Another study found that up to 81.4% of IUA patients had improved menstruation and were implanted with an IUB after surgery [1], the overall conception rate was 33.9%-48.1%, and the recurrence rate of IUA after surgery was 13.6%-38.7% [12][13][14][15][16]. Compared with placing an IUD after TCRA, insertion of an IUB can lead to a lower readhesion AFS score and a lower recurrence rate [1], which is entirely consistent with the results in this study.…”
Section: Results In the Context Of What Knownmentioning
confidence: 99%
“…Oral administration of 9 mg/diet estrogen before TCRA and 10 mg/ diet after TCRA improved pregnancy rates and menstrual cycles in patients with moderate or severe IUA (Liu AZ et al, 2016); however, estrogen therapy may increase the risk of cancer (Rossouw et al, 2002) and venous thrombosis (Bracamonte and Miller, 2001). Balloon dilatation after TCRA and early second-look hysteroscopy improved pregnancy outcomes (Sun et al, 2020), and the appropriate delay of balloon placement in the uterine cavity prevented re-adhesion but was not effective in severe IUA (Zhang et al, 2021a). The dilated balloon is a nonvariable sphere that is not able to be plasticized according to the shape of the uterine cavity, resulting in ineffective improvement of adhesions in the uterine horns (Sun et al, 2020).…”
Section: Intrauterine Adhesionmentioning
confidence: 99%
“…Balloon dilatation after TCRA and early second-look hysteroscopy improved pregnancy outcomes (Sun et al, 2020), and the appropriate delay of balloon placement in the uterine cavity prevented re-adhesion but was not effective in severe IUA (Zhang et al, 2021a). The dilated balloon is a nonvariable sphere that is not able to be plasticized according to the shape of the uterine cavity, resulting in ineffective improvement of adhesions in the uterine horns (Sun et al, 2020). IVF after TCRA improved reproductive outcomes, but increased the miscarriage rate .…”
Section: Intrauterine Adhesionmentioning
confidence: 99%